2016
DOI: 10.1186/s12885-016-2051-5
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of KIT and PDGFRA mutational status with clinical benefit in patients with gastrointestinal stromal tumor treated with sunitinib in a worldwide treatment-use trial

Abstract: BackgroundSeveral small studies indicated that the genotype of KIT or platelet-derived growth factor receptor-α (PDGFRA) contributes in part to the level of clinical effectiveness of sunitinib in gastrointestinal stromal tumor (GIST) patients. This study aimed to correlate KIT and PDGFRA mutational status with clinical outcome metrics (progression-free survival [PFS], overall survival [OS], objective response rate [ORR]) in a larger international patient population.MethodsThis is a non-interventional, retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 36 publications
1
40
1
1
Order By: Relevance
“…Heterodimerization of PDGFRA allows its transactivation with other signaling components, along with its ability to work independently and entering a vicious cycle via autocrine or paracrine stimulation. The implication of PDGFRA in various cancers is evident, yet there is no research on the role of PDGFRA in head and neck squamous cell carcinoma. Hence, the aim of this study was to quantify the expression of PDGFRA in oral SCC and find its relationship with tumor features and patient cancer outcomes…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Heterodimerization of PDGFRA allows its transactivation with other signaling components, along with its ability to work independently and entering a vicious cycle via autocrine or paracrine stimulation. The implication of PDGFRA in various cancers is evident, yet there is no research on the role of PDGFRA in head and neck squamous cell carcinoma. Hence, the aim of this study was to quantify the expression of PDGFRA in oral SCC and find its relationship with tumor features and patient cancer outcomes…”
Section: Discussionmentioning
confidence: 99%
“…The role of EGFR and VGFR in oncogenesis and neovascularization is established but that of PDGFRA is unclear. The role of the PDGFRA signaling pathway is evident in various cancers . The authors believe that a research directed toward the common events in tumorigenesis and progression among heterogeneous tumors could provide a potential target for therapy in majority of the cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with exon 9 mutations require an escalated dose of imatinib [25], whereas certain patients, especially those with exon 11 mutations, show no benefit from imatinib dose escalation [26]. More recent studies [27,28] showed improved efficacy in sunitinib-treated patients with primary mutations in KIT exon 9 compared with exon 11. A limitation of the current study is that correlation between mutational status and sunitinib efficacy and safety were not examined.…”
Section: Discussionmentioning
confidence: 99%
“…It has become increasingly important to genotype GISTs, as not all genotypes respond equally to TKIs. These advances in the diagnosis and treatment of GIST have changed rapidly and dramatically over the past decade.…”
Section: Introductionmentioning
confidence: 99%